1987
DOI: 10.1111/j.1600-0773.1987.tb01815.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Sodium‐Poor Diet on Lithium Clearance at Different Dietary Potassium Contents in Rats

Abstract: In rats on a diet with a sodium content of 300 mmol/kg, lithium is reabsorbed exclusively in the proximal tubules, and lithium clearance (CLi) equals the proximal tubular fluid output (Vprox). In rats on a sodium-poor diet (5 mmol/kg), lithium is also reabsorbed in the distal nephron and CLi is therefore lower than Vprox. The present paper examines the reduction of CLi in response to a low sodium diet in Brattleboro rats with hereditary diabetes insipidus maintained on different dietary potassium contents. CLi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated that in rats subjected to potassium depletion, both C Li and the fractional excretion of lithium (FE Li ) are considerably reduced (Shirley & Walter, 1986; Thomsen & Leyssac, 1987; Shirley, Zewde & Walter, 1990), which on the face of it suggests a reduction in end‐proximal fluid delivery. This conclusion is supported by the observation that in Brattleboro rats, which lack vasopressin, the reduction in C Li during potassium depletion is accompanied by a reduction in urine flow rate (Thomsen & Leyssac, 1987); in the absence of vasopressin, changes in urine flow rate are thought to reflect changes in fluid delivery from the proximal tubules (Shirley, Walter & Thomsen, 1983; Levinsky & Lieberthal, 1992). More direct evidence for a reduced end‐proximal fluid delivery during potassium depletion comes from micropuncture studies in which enhanced fractional fluid reabsorption in the proximal convoluted tubules has been reported (Capasso, Kinne, Malnic & Giebisch, 1986; Walter, Shore & Shirley, 1988).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that in rats subjected to potassium depletion, both C Li and the fractional excretion of lithium (FE Li ) are considerably reduced (Shirley & Walter, 1986; Thomsen & Leyssac, 1987; Shirley, Zewde & Walter, 1990), which on the face of it suggests a reduction in end‐proximal fluid delivery. This conclusion is supported by the observation that in Brattleboro rats, which lack vasopressin, the reduction in C Li during potassium depletion is accompanied by a reduction in urine flow rate (Thomsen & Leyssac, 1987); in the absence of vasopressin, changes in urine flow rate are thought to reflect changes in fluid delivery from the proximal tubules (Shirley, Walter & Thomsen, 1983; Levinsky & Lieberthal, 1992). More direct evidence for a reduced end‐proximal fluid delivery during potassium depletion comes from micropuncture studies in which enhanced fractional fluid reabsorption in the proximal convoluted tubules has been reported (Capasso, Kinne, Malnic & Giebisch, 1986; Walter, Shore & Shirley, 1988).…”
mentioning
confidence: 99%
“…Further evidence for competitive inhibition of Li + reabsorption by Na + in K-depleted rats comes from studies in which the tubular Na + concentration in the distal-nephron has been reduced by administration of a low-Na + diet in addition to a low-K + diet. These studies [4,15] have repeatedly demonstrated that FE Li is reduced to almost zero, indicating almost complete reabsorption of Li + by the amiloride-sensitive site when competition from tubular Na + is severely reduced.…”
Section: Effect Of K + Restriction On LI + Reabsorption In the Distalmentioning
confidence: 99%
“…Dietary K + restriction also leads to hyperpolarization of the apical membrane of the collecting ducts [14], and a decrease in the amount of Na + delivered to the amiloride-sensitive segment to K + -depleted rats has been demonstrated to increase distal tubular Li + reabsorption to almost 100% [4,15]. Apical membrane hyperpolarization of the cortical collecting ducts thus appears to be important in conditions associated with distal tubular Li + reabsorption, and the delivery of Na + to the amiloride-sensitive sites seems to be of utmost importance for the magnitude of distal tubular Li + reabsorption.…”
Section: Introductionmentioning
confidence: 99%
“…but it has also been demonstrated that the method cannot be used in rats and dogs given a low sodium diet because this leads to distal lithium reabsorption [4,11,18,[24][25][26]. W hether any reabsorption of lithium occurs in the distal ne phron when humans are maintained on a low sodium diet remains to be established [3,14).…”
Section: Introductionmentioning
confidence: 99%